(untitled) (International Journal of Engineering and Computer Science, 2014)
Presently, a very large amount of data stored in databases is increasing at a tremendous speed. This growing need gives a view for a new research field called Knowledge Discovery in Databases (KDD) or Data Mining, which attract attention from researchers in from various fields which includes Database Design, Statistics, Pattern Recognition, Machine Learning, and Data Visualization et,. In this survey approximately 40 research papers were collected concerning various fields in data mining and discussed each and categorized them under the few areas and the trends was interpreted based on the area of research and applications.